Reprezentacje obiektów przyrodniczych z dziecięcej perspektywy - Monika Wiśniewska-Kin; Eliza Rybska (Problemy Wczesnej Edukacji)
In presented article we have described examples of children’s strategies for meaning fulfilment in the verbal and visual code. In conducted research, we attempted to reconstruct children’s abilities of conceptualizing objects with (1) prototypical, (2) prototypical and individual features, and (3) nonprototypical features. We were interested also in children’s methods of categorization (recognizing an object at various levels of abstraction) and constructing knowledge in terms of selected domains (appearance, environment, behavior and the relationship between animals and humans). 170 children of two age groups (3/4 and 4/5 years old) participated in the study. They were first asked to recognize an object on the basis of selected features shown in pictures. Then children were interviewed and asked to make a drawing. Research has shown that exposing children to a fragment of an image allows them to recognize the whole object and express their personal knowledge. The presented research showed also that children make conceptualization mainly through personal experiences and that when describing animals, children focus on observable animal activity and behavior, as well as animal appearance, size, the environment of living and the relation with humans.